Metal Mountable Miniature Folded Patch Tag Antennas Fed by Coplanar Waveguide - Moh, Cai Wei (2019)
In this dissertation, two projects have been conducted for studying the techniques to miniaturize the footprints of two metal mountable UHF RFID tag antennas. To prove the validity and reliability of the proposed tags, prototypes have been made and measured. First, a folded patch, which is centrally fed by a coplanar feedline, is proposed for designing a miniature UHF tag antenna for mounting on metal surfaces. In the design, two notches have been incorporated with an inductive stub for tuning of the tag’s resonance over a larger frequency range. The proposed tag can achieve a read distance of greater than 10 m when placed on metal plate and beyond 5 m when it is placed on different dielectric slabs. In the second project, a pair of differentially fed coplanar waveguides is employed for exciting a folded patch antenna for designing a metal mountable UHF RFID tag. Multiple slots are incorporated into the patch for tuning the resonant frequency and optimizing the impedance matching between the chip and the antenna. Two inductive stubs are introduced at the two corners of the radiating patch to enable further frequency tuning. The read range of the proposed tag can achieve 8.9 m when tested on metal plate. The read distance is also more than 4m when attached to various dielectric materials. Both of the projects can be directly fabricated on the single surface of a single piece onPET (polyethylene terephthalate). No vias or additional structures are needed in the designs, making the design processes simple and easy.